Applying the theoretical domains framework and behavior change wheel to inform interventions for food and food-related waste audits in hospital foodservices - Cook, Nathan; Collins, Jorja; Porter, Judi; Goodwin, Denise (Frontiers in Nutrition, 2023)
Background: Completing aggregate food and food-related waste audits in hospital foodservices is an intense practice, however they can demonstrate problem areas that require attention to reduce waste. Identifying interventions to facilitate and improve the implementation of these audits can be guided by behavior change science. The aims of this study were to use behavior change theories and frameworks to (1) describe the drivers of behavior to complete food and food-related waste audits and (2) identify possible interventions that support the implementation and uptake of these audits.Methods: Purposive sampling was used to recruit participants from hospitals in Victoria, Australia who worked in their foodservice system. Semi-structured interviews sought knowledge of participants perceived barriers and enablers to completing food and food-related waste audits. Deductive analysis using the Theoretical Domains Framework (TDF) and Capability Opportunity Motivation Behavior theory (COM-B) identified dominant drivers of behavior. TDF domains were then matched to their corresponding intervention functions according to the Behavior Change Wheel framework (BCW) to identify relevant strategies that may support audit implementation.Results: Data from 20 interviews found the dominant COM-B constructs (TDF domains) were psychological capability (knowledge, skills), physical opportunity (environmental context and resources) and reflective motivation (social/professional role and identity, beliefs about capabilities). These dominant domains come from narratives that participants shared about foodservice staffs' lack of knowledge, labor, time and the hospital avoiding responsibility for audit completion. Corresponding intervention functions that could have the most potential for implementing waste audits were education, training, environmental restructuring, modelling and enablement. Participants' shared perspectives of audit enablers resembled these: for example, obtaining staff buy-in, reinforcing behavior through incentives and installing an audit champion.To transition towards regular food and food-related waste auditing practices in hospital foodservices these findings may help identify practice and policy change that delivers standardized auditing activities to encourage long term behavior change. Interventions to support audit completion should address each behavioral construct and relevant domain, as individual hospital sites will experience unique contextual factors and expectations influencing audit outcomes. A co-design process that includes staff and stakeholders of hospital foodservices is recommended to enable engagement and practical solutions to audit implementation.